Structural insights for neutralization of Omicron variants BA.1, BA.2, BA.4, and BA.5 by a broadly neutralizing SARS-CoV-2 antibody - Kumar, Sanjeev; Patel, Anamika; Lai, Lilin; Chakravarthy, Chennareddy; Valanparambil, Rajesh; Reddy, Elluri Seetharami; Gottimukkala, Kamalvishnu; Davis-Gardner, Meredith E.; Edara, Venkata Viswanadh; Linderman, Susanne; Nayak, Kaustuv; Dixit, Kritika; et al. (Science advances, 2022)
In this study, by characterizing several human monoclonal antibodies (mAbs) isolated from single B cells of the COVID-19–recovered individuals in India who experienced ancestral Wuhan strain (WA.1) of SARS-CoV-2 during early stages of the pandemic, we found a receptor binding domain (RBD)–specific mAb 002-S21F2 that has rare gene usage and potently neutralized live viral isolates of SARS-CoV-2 variants including Alpha, Beta, Gamma, Delta, and Omicron sublineages (BA.1, BA.2, BA.2.12.1, BA.4, and BA.5) with IC 50 ranging from 0.02 to 0.13 μg/ml. Structural studies of 002-S21F2 in complex with spike trimers of Omicron and WA.1 showed that it targets a conformationally conserved epitope on the outer face of RBD (class 3 surface) outside the ACE2-binding motif, thereby providing a mechanistic insights for its broad neutralization activity. The discovery of 002-S21F2 and the broadly neutralizing epitope it targets have timely implications for developing a broad range of therapeutic and vaccine interventions against SARS-CoV-2 variants including Omicron sublineages. A rare human monoclonal antibody neutralizes all SARS-CoV-2 Omicron variants by targeting a conserved epitope on the RBD.